Analisis Kemampuan Membaca Kitab Gundul Menggunakan Metode Sorogan Di Pondok Pesantren Sunan Ampel Denanyar Jombang - Nurul Hidayah; Siti Naimah (Program Studi Pendidikan Bahasa Arab (PBA) Sekolah Tinggi Ilmu Tarbiyah Pemalang, 2022)
This paper discusses the ability of students of Pondok Pesantren Sunan Ampel Denanyar Jombang in reading bald books. This paper is motivated by the method used in Boarding Schools to overcome the difficulty of students in reading bald books. Bald book is a tradition learned in Pondok Pesantren and has become a label in education in Pondok Pesantren. Sorogan method is one of the methods in learning to read bald books. In this case the author aims to conduct research on the ability of students in Pondok Pesantren Sunan Ampel Denanyar Jombang in reading the bald book which in his learning using the sorogan method. The method used in this study is descriptive qualitative research using (Field Research). The types of data used in this study are primary and secondary data taken from related sources. The discussion showed the analysis in Pondok Pesantren Sunan Ampel Denanyar Jombang in reading the bald book using sorogan method has reached a satisfactory value. This can be seen from the value of the research results to some students in Pondok Pesantren Sunan Ampel Denanyar Jombang.